MARKETING FUNCTION OF WHITE PEPPER ON CV. INDO BAKTI MAKMUR VILLAGE DUL DISTRICT BASE CENTRAL BANGKA REGENCY: FUNGSI PEMASARAN LADA PUTIH DI CV. INDO BAKTI MAKMUR DESA KAMPUNG DUL KECAMATAN PANGKALAN KABUPATEN BANGKA TENGAH - Yulia Yulia (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
White pepper is one of the most important types of spices among other spices both in terms of its role in donating foreign exchange and in terms of its very distinctive uses and can not be replaced with other spices. This study aims to identify the marketing functions of white pepper in CV.Indo Bakti Makmur. Research methods used case study methods. Data analysis using qualitative descriptive methods. The results showed that the marketing functions in CV.Indo Bakti Makmur is divided into three main functions, namely the first exchange function in which there is a purchase function and sales function, then the second physical function, in which there is a storage function, transportation function, and physical form change function then the third is the function of the provider of facilities in which there is a function about market information , risk management, and the process of standardization or grading